Genetic Variation Of Kelampayan (Neolamarckia Cadamba) Trees For Planted Forest Development In Sarawak - Tan, Sze Leng; Julaihi, Abdullah; Ho Wei, Seng (2007)
Neolamarckia cadamba is now a commercially important plantation species, and is seen slowly but surely replacing other exotic species. Therefore, it is crucial that we have the tools to determine the genetic variation of N. cadamba that occurs in Sarawak, both for natural and planted populations. The objective of this study is to assess the genetic variation of N. cadamba from different areas in Sarawak by random amplified polymorphic DNA (RAPD) markers. To date, leaf samples from a total of 162 individual trees have been collected from five populations, namely: Matang, Sabal and Simunjan, Bintulu, Miri and Sibu. Total genomic DNA is isolated from the silicagel‐ preserved leaf samples, and subsequently the isolated DNA is analysed using RAPD technique. The RAPD marker detects DNA variations that result in the loss or gain of DNA fragments at a particular location in the Kelampayan genome. These variations will help us determine genetic relatedness and diversity between different Kelampayan populations. The results of this study will provide a foundation in the selection of plus trees, establishment of forest seed production areas, and subsequently production of high quality seedlings for plantations with all the desirable characteristics in term of growth rate, bole form, wood density and disease resistance.